Hyperthermia due to heat retention in chronic spinal cord injury: A case report. (9th January 2019) - Tomoda, Yoshitaka; Kagawa, Satoshi; Kurata, Satoshi; Tanaka, Kazutoyo
Abstract: An 80‐year‐old male with past history of cervical spinal cord injury visited our hospital owing to perforation in the digestive tract. Upon admission to the general ward, he presented with a sustained fever that was unresponsive to acetaminophen and antibiotics. Based on the dry skin and underlying disease, he was diagnosed with hyperthermia due to heat retention. After controlling the room temperature to cool his body and performing evaporative and convective cooling, his symptoms completely resolved. This case highlights that primary physicians should be aware of thermoregulatory dysfunction in patients with cervical spinal cord injury. Abstract : We present a case of an 80‐year‐old male with chronic cervical spinal cord injury who presented with high fever. Based on dry skin and underlying disease, he was diagnosed with hyperthermia due to heat retention. His symptoms completely resolved after controlling the room temperature and cooling his body.